Effects of Borreria latifolia (Aubl.) K. Schum. and Rosmarinus officinalis L. as feed additives on performance and meat quality of finishing village chicken - Ameer, Ali Abdul (2016)
The poultry industry would extremely appreciate natural antioxidants that could replace synthetic ones and satisfy consumer demands for food products without residues from substances that can possibly hurt human health. Besides health decay, lipid oxidation is also a major cause of meat quality deterioration, affecting color, flavor, texture, and nutritional value. The objective of this study was to investigate the impact of dietary supplementation of Borreria latifolia and Rosmarinus officinalis as natural antioxidant on performance and meat quality of finishing village chicken. Two experiments were conducted, the first experiment was to confirm the antioxidant activity of BL through a comparison with Rosmarinus officinalis (RO) as a reference in addition to evaluate their effect on performance and meat quality. Three treatments were employed: T1 (control basal diet without supplementation), T2 (basal diet with 1% of BL), T3 (basal diet with 1% of RO). There was a significant difference (p < 0.05) between dietary treatments in cooking loss value. Cooking loss value was higher in T1 compared to the T2 and T3. Significantly (p < 0.05), pH value was affected by dietary treatments with T2 and T3 having higher pH value compared to T1. Additionally, significant effect of dietary treatments was recorded during sensory evaluation test whereas T2, T3 had a higher score in overall acceptability compared to control with T2 higher (p < 0.05) than T3. Moreover, significant effect (p < 0.05) of dietary treatment on lipid oxidation value was observed. T2 and T3 had a lower malondialdehyde (MDA) concentrations compared to T1. Additionally, there was significant (p < 0.05) difference between males and female detected in final body weight, weight gain, feed intake, carcass weight, breast and thigh weight, wing weight, neck and loin weight. Moreover, the sex effect was significant (p < 0.05) on MUFA, PUFA, PUFA:SFA ratio, n6:n3 ratio, pH value, yellowness (b*) and lipid oxidation. In addition, significant (p < 0.05) increase in tenderness, pH, and lipid oxidation through post mortem aging period (1, 3, 5 d) were recorded, while cooking loss (CL) and redness (a*) were decreased. Significant interactions between herb and sex on pH parameter, and herb by sex, herb by post-mortem period, sex by postmortem period, and herb by sex by post-mortem period interactions in regards with lipid oxidation were observed. The second experiment was to evaluate the effect of three different levels of BL on meat quality and growth performance. Four treatments applied were: T1 (control basal diet without supplementation), T2 (basal diet with 1.5% of BL), T3 (basal diet with 2% of BL), and T4 (basal diet with 2.5% of BL). There was a significant (p < 0.05) effect of the dietary treatments on redness (a*) value. T4 showed higher value than T1, T2, and T3. Furthermore, T4 produced higher (p < 0.05) scores than T1, T2, and T3 in both overall acceptability and texture through sensory evaluation test. With regard to lipid oxidation test, T4 showed the lowest malondialdehyde concentration whereas T1 had the highest concentration of MDA. Meanwhile, T2 and T3 had a higher concentration of MDA compared to T4. Furthermore, there was significant (p < 0.05) difference between males and females in MUFA, PUFA, PUFA:SFA ratio, n6:n3 ratio, yellowness (b*) and lipid oxidation. In addition, significant (p < 0.05) effect of sex on final body weight, weight gain, feed intake, carcass weight, breast and thigh weight, wings weight, neck and loin weight, and liver weight was recorded. The obtained result of the current studies showed significant (p < 0.05) decreases in redness (a*) and cooking loss (CL) during post mortem aging period while pH value, tenderness, and lipid oxidation were elevated. Additionally, there were significant interactions between herb and sex, herb and aging period, sex and aging period, and the herb by sex by aging period interaction on lipid oxidation as well as a significant interaction between herb and sex on pH was noticed in the study. Generally, the present study revealed that dietary supplementation of 2.5% BL improved oxidative stability which could have extended meat shelf life and may enhance meat acceptability including a partial improvement in meat color. While, the enhancement of growth performance was not revealed.